Specificity for the correlation between the body surface and viscera in the pathological state of COPD: A prospective, controlled, and assessor-blinded trial - Jiang, Yongliang; Hu, Hantong; He, Xiaofen; Li, Xiaoyu; Zhang, Yajun; Lou, Jiali; Wu, Yuanyuan; Fang, Junfan; Shao, Xiaomei; Fang, Jianqiao (Frontiers in Physiology, 2023)
Background: The association between the body surface and viscera remains obscure, but a better understanding of the body surface-viscera correlation will maximize its diagnostic and therapeutic values in clinical practice. Therefore, this study aimed to investigate the specificity of body surface-viscera correlation in the pathological state. Methods: The study subjects included 40 participants of chronic obstructive pulmonary disease (COPD) in the COPD group and 40 age-matched healthy participants in the healthy control group. Laser doppler flowmetry, infrared thermography, and functional near-infrared spectroscopy were respectively adopted to measure (1) the perfusion unit (PU), (2) temperature, and (3) regional oxygen saturation (rSO2) of 4 specific sites distributing in the heart and lung meridians. These 3 outcome measures reflected the microcirculatory, thermal, and metabolic characteristics, respectively. Results: Regarding the microcirculatory and thermal characteristics of the body surface, the PU and temperature of specific sites on the body surface (i.e., Taiyuan (LU9) and Chize (LU5) in the lung meridian) in the COPD group were significantly increased compared with healthy controls (P<0.05), whereas PU and temperature of other sites in the heart meridian (i.e., Shenmen (HT7) and Shaohai (HT3)) did not change significantly (P>0.05). Regarding the metabolic characteristics, rSO2 of specific sites in the lung meridian (i.e., Taiyuan (LU9) and Chize (LU5)) and Shaohai (HT3) of the heart meridian in the COPD group was significantly decreased compared with healthy controls (P<0.01), whereas rSO2 of Shenmen (HT7) in the heart meridian did not change significantly (P>0.05). Conclusions: In the disease state of COPD, the microcirculatory, thermal, and metabolic characteristics of specific sites on the body surface in the lung meridian generally manifest more significant changes than those in the heart meridian, thereby supporting relative specificity for the body surface-viscera correlation in the pathological state.